2021
DOI: 10.1155/2021/6638249
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Treatment of Tendon Stem/Progenitor Cells Reduces Cellular Senescence by Upregulating Autophagy

Abstract: The elderly population is prone to tendinopathy due to aging-related tendon changes such as cellular senescence and a decreased ability to modulate inflammation. Aging can render tendon stem/progenitor cells (TSCs) into premature senescence. We investigated the effects of rapamycin, a specific mTOR inhibitor, on the senescence of TSCs. We first showed that after treatment with bleomycin in vitro, rat patellar TSCs (PTSCs) underwent senescence, characterized by morphological alterations, induction of senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Previous studies reviewed the relations between cellular senescence and autophagy [ 30 , 31 ] and suggested that autophagy plays a dual role in the regulation of MSC senescence. Upregulation of autophagy can decrease the apoptosis of aged MSCs in the condition of myocardial infarction [ 34 , 35 ], restore the biological properties of aged MSCs [ 76 ], rejuvenate MSCs derived from patients with idiopathic pulmonary fibrosis [ 49 ], and reduce the senescence of patellar tendon stem/progenitor cells [ 77 ]. Compared with young MSCs, aged MSCs have significantly reduced autophagic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reviewed the relations between cellular senescence and autophagy [ 30 , 31 ] and suggested that autophagy plays a dual role in the regulation of MSC senescence. Upregulation of autophagy can decrease the apoptosis of aged MSCs in the condition of myocardial infarction [ 34 , 35 ], restore the biological properties of aged MSCs [ 76 ], rejuvenate MSCs derived from patients with idiopathic pulmonary fibrosis [ 49 ], and reduce the senescence of patellar tendon stem/progenitor cells [ 77 ]. Compared with young MSCs, aged MSCs have significantly reduced autophagic activity.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy might derive from the different concentrations of rapamycin and thus the diffident regulation on autophagic flux. Rapamycin was initially found as an antifungal macrocyclic lactone, then approved for preventing allograft rejection, restenosis, and stent thrombosis [ 40 ]. It has been shown that rapamycin induces autophagy by inhibiting mTORC1 signaling, which is a master regulator in the response to nutrient availability and growth factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a gerostatic, rapamycin suppresses growth and senescence in yeast [71] and mammalian cells [32,[40][41][42][72][73][74][75][76][77][78][79][80][81][82]. Rapamycin slows aging, stem cell exhaustion and extends lifespan in the simplest organism: Hydra [83].…”
Section: Gerostatics In Life Extensionmentioning
confidence: 99%
“…It could be due to reduction of these markers per cell, or even cell rejuvenation. In fact, rapamycin, which does not kill senescent cells, decreases expression of SA-β-gal and p16 [ 73 , 74 , 152 ]. In the organism, low doses of rapamycin decrease levels of p16 and tend to decrease SA-β-gal activity [ 153 ].…”
Section: Introductionmentioning
confidence: 99%